INOVASI TEKNOLOGI PEMBUATAN TERRARIUM BERBASIS LINGKUNGAN DI SMA NEGERI 2 KAHAYAN TENGAH - Sunariyati, Siti; Arifin, Samsul; Anggoro, Rahayu Opi (Jurnal Abdi Insani, 2025)
This community service activity aims to improve the understanding of ecosystem concepts, improve practical skills, and technological literacy of students at SMA Negeri 2 Kahayan Tengah through socialization and training in making environmentally-based terrariums innovated by Internet of Things (IoT) technology. The implementation method includes preparation, training, mentoring, monitoring, and evaluation involving 25 students and 5 teachers. Data was obtained through activity documentation, pre-post tests and student response questionnaires. The results of the activity showed a significant increase in student knowledge with an average pre-test score of 50.83 increasing to 82.40 in the post-test, achieving an N-Gain of 0.61 categorized as medium. Student responses were also highly positive, with 85% rating the activity as engaging, 82% reporting increased environmental awareness, 75% feeling more motivated to learn science, and 80% considering the program relevant to the Merdeka Curriculum. The terrarium products created by students reflected creativity and potential to be further developed as both innovative learning media and marketable products. This program contributes to the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) while introducing IoT applications as an innovation in environment-based education.